2019
DOI: 10.3389/fmicb.2019.00995
|View full text |Cite
|
Sign up to set email alerts
|

Oil Hydrocarbon Degradation by Caspian Sea Microbial Communities

Abstract: The Caspian Sea, which is the largest landlocked body of water on the planet, receives substantial annual hydrocarbon input from anthropogenic sources (e.g., industry, agriculture, oil exploration, and extraction) and natural sources (e.g., mud volcanoes and oil seeps). The Caspian Sea also receives substantial amounts of runoff from agricultural and municipal sources, containing nutrients that have caused eutrophication and subsequent hypoxia in the deep, cold waters. The effect of decreasing oxygen saturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…7 ), consistent with the significantly higher losses of PAHs from these treatments compared to diesel amendments ( Fig. 2C and D ) and with previous reports of aromatic hydrocarbon biodegradation by Amphritea ( 50 52 ). MAGs with novel classifications in the Genome Taxonomy Database (GTDB) exhibiting hydrocarbon biodegradation potential included Sphingorhabdus_ A, 50-400-T64, Pseudomonas _ D, and PGZG01 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…7 ), consistent with the significantly higher losses of PAHs from these treatments compared to diesel amendments ( Fig. 2C and D ) and with previous reports of aromatic hydrocarbon biodegradation by Amphritea ( 50 52 ). MAGs with novel classifications in the Genome Taxonomy Database (GTDB) exhibiting hydrocarbon biodegradation potential included Sphingorhabdus_ A, 50-400-T64, Pseudomonas _ D, and PGZG01 ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…However, after the 15th subculture, they still grew in all consortia, except in C4. Those Gammaproteobacteria were regularly discovered in the oil-impacted marine environments and were found competent in degrading oil [39]. They were also explored for their ability to degrade low molecular weight alkanes, aromatics, BTEX (benzene, toluene, ethylbenzene and xylenes), proline, catechol, cyclohexanone, and nitroalkanes.…”
Section: Discussionmentioning
confidence: 99%
“…A microcosm study [ 81 ] reported better degradation of 19 and 21C aliphatic chains under anoxic than oxic conditions. In the same study, heavy aliphatic hydrocarbons (>28C) were completely degraded in oxic microcosms but not in anoxic.…”
Section: Metabolic Mechanisms Of Bacterial Biodegradation Of Hydromentioning
confidence: 99%
“…In anoxic microcosms, most but not all the EPA16 compounds were degraded, with benz(a)anthracene and chrysene being particularly effectively degraded. A higher proportion of dibenzothiophene was degraded in anoxic than oxic microcosms [ 81 ].…”
Section: Metabolic Mechanisms Of Bacterial Biodegradation Of Hydromentioning
confidence: 99%